Determining the best alternative to build and operate a new coal crushing facilities: Analytical hierarchy process approach - Simatupang, Kondar Paido; Wasesa, Meditya (Goodwood Publishing, 2024)
Purpose: This study examines the increase in national coal production in Indonesia and its impact on PT. KLM is one of the largest coal producers in Indonesia. With rising production and shifting global market needs, this study aims to analyze the necessity of building a new Coal Crushing Facility next to the South Pinang Extension #2 area, including evaluating costs and the best strategies for its implementation. Research Methodology: The research methodology involved analyzing problem trees and stakeholders to uncover business complexities and identify the root causes of issues. Qualitative data were collected through semi-structured interviews. All alternatives were evaluated using Value-Focused Thinking (VFT), and the Analytic Hierarchy Process (AHP) method was employed to determine the best alternative assisted by the Super Decision application. Results: Based on interviews conducted with subject matter experts (SMEs) and analysis, three funding solutions were identified: 1. owned by self-financing, and (2) Own by Leasing 3. Rental Scheme. Conclusions: The study concludes that building a new Coal Crushing Facility at South Pinang Extension is necessary to support rising production, with three viable financing alternatives self-financing, leasing, and rental identified through systematic analysis to ensure efficiency and competitiveness. Limitations: The limitations of this study are that it was sourced from an internal company and data were gathered from outside the company. An alternative option was developed based on extensive collaborative discussions and interview sessions with subject matter experts within the company. Contribution: This study provides valuable guidelines for selecting alternative financing to build and operate new coal-crushing facilities at South Pinang Extension #2.